The state public servant's insight towards the star-rating system / Mohd Feqree Fezwan Abdul Aziz and Nur Yuannie Azurianty Mohd Idris - Abdul Aziz, Mohd Feqree Fezwan; Mohd Idris, Nur Yuannie Azurianty (2014)
This research is about the State Public Servant's Insight Towards The Star-Rating System which presented three objectives; to study the perception of the state public servants towards the Star-Rating System, to evacuate the relationship between workload, response to change and the perception towards the Star-Rating System and to determine differences in the perception of the state public servants towards the Star-Rating System across different background of service group, service tenure and gender. The study was conducted towards the public organisation which involve in the Star-Rating Program by distributing them with the questionnaires. The SPSS version was used to design the data and test upon the research study. In order to make the clear explanation to prove the findings, several methods were used such as Mann-Whitney test, Kruskal Wallis test, Spearman and Chi Square test.